Synthesis of Polycyclic Amines through Mild Metal‐Free Tandem Cross‐Dehydrogenative Coupling/Intramolecular Hydroarylation of N‐Aryltetrahydroisoquinolines and Crotonaldehyde. Issue 3 (12th December 2014) - Wu, Xiang; Chen, Dian‐Feng; Chen, Shu‐Sen; Zhu, Yi‐Fan
Abstract: A [4+2] cycloaddition reaction proceeding through tandem cross‐dehydrogenative coupling/intramolecular hydroarylation between N ‐aryltetrahydroisoquinolines and crotonaldehyde was developed by virtue of enamine–iminium catalysis, which enabled the rapid construction of ring‐fused tetrahydroquinolines. The first metal‐free catalytic oxidative coupling of γ‐selective C(sp 3 )–H bonds of crotonaldehyde was realized by using a secondary amine catalyst and 2, 3‐dichloro‐5, 6‐dicyanoquinone. Abstract : Tandem oxidative cross‐dehydrogenative coupling/intramolecular hydroarylation between N ‐aryltetrahydroisoquinolines and crotonaldehyde enables the rapid construction of ring‐fused tetrahydroquinolines. The first metal‐free catalytic oxidative coupling of γ‐selective C(sp 3 )–H bonds of crotonaldehyde is realized by using a secondary amine catalyst and 2, 3‐dichloro‐5, 6‐dicyanoquinone (DDQ).